Successful treatment and long‐term outcome of a traumatic urethral laceration in a 3‐week‐old puppy. Issue 3 (26th May 2021) - Esposito, Fabio; Cinti, Filippo; Minei, Sergio; Pisani, Guido
Abstract: A 3‐week‐old male German Shepherd was referred to treat the complications of a first intervention following a bite injury occurring a few hours after birth. Physical examination revealed preputial stenosis, with urine collection in the preputial fornix and deep lacerations of the glans and urethra. Prepuce resection and partial penile amputation followed by prescrotal urethrostomy was performed to treat the clinical condition. The immediate postoperative follow‐up showed good conditions of the surgical wound and normal urinary flow. The dog had a normal stoma size without dysuria at the latest follow‐up examination 4 years post‐operatively. Despite the young age of the patient, the prescrotal urethrostomy treatment was successful at short‐ and long‐term follow‐up, without complications.